1998
DOI: 10.1093/emboj/17.22.6660
|View full text |Cite
|
Sign up to set email alerts
|

Differential viral induction of distinct interferon-alpha genes by positive feedback through interferon regulatory factor-7

Abstract: Interferon (IFN) genes are among the earliest transcriptional responses to virus infection of mammalian cells.Although the regulation of the IFNβ gene has been well characterized, the induction of the large family of IFNα genes has remained obscure. We report that the IFNα genes can be divided into two groups: an immediate-early response gene (IFNα4) which is induced rapidly and without the need for ongoing protein synthesis; and a set of genes that display delayed induction, consisting of at least IFNα2, 5, 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

46
936
3
5

Year Published

2002
2002
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 967 publications
(990 citation statements)
references
References 56 publications
46
936
3
5
Order By: Relevance
“…Combined with a recent report that three zebrafish IFNs can directly induce the expression of themselves (LopezMunoz et al, 2009), this result suggested that fish IFN genes belong to ISGs group. In mammals, IFN␤ is an early phase IFN and can prime the expression of later phase IFN genes other than itself (Deonarain et al, 2000;Marie et al, 1998;Sato et al, 2000), and IFN␣ cannot be induced by itself (Ank et al, 2006). In contrast, type III IFNs are induced directly by type I IFNs and also themselves (Ank et al, 2008;Ank et al, 2006;Osterlund et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Combined with a recent report that three zebrafish IFNs can directly induce the expression of themselves (LopezMunoz et al, 2009), this result suggested that fish IFN genes belong to ISGs group. In mammals, IFN␤ is an early phase IFN and can prime the expression of later phase IFN genes other than itself (Deonarain et al, 2000;Marie et al, 1998;Sato et al, 2000), and IFN␣ cannot be induced by itself (Ank et al, 2006). In contrast, type III IFNs are induced directly by type I IFNs and also themselves (Ank et al, 2008;Ank et al, 2006;Osterlund et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…In mammals, activation of IRF3 is sufficient for the expression of early phase IFNs and in turn, the produced early phase IFNs are required for the expression of later phase IFN genes. In the latter case, IRF7 is necessary but, prior to its action, it has to be synthesized through the IFN␤-activated Stat1 pathway (Marie et al, 1998;Sato et al, 2000). IRF3 and IRF7 seem to play similar roles in regulation of type III IFNs (Ank et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The expression of type I IFN genes is tightly regulated, and IRF-3 is known to be involved in induction of IFN-b and IFN-a4 in response to virus. 9,25 Induction of IFN-a5 was previously described to be dependent on the IRF-7 transcription factor induced by IFN. 25 Our analysis now identifies IFN-a5 as an IRF-3-dependent direct response gene.…”
Section: Irf-3-dependent Direct Response Genesmentioning
confidence: 99%
“…9,25 Induction of IFN-a5 was previously described to be dependent on the IRF-7 transcription factor induced by IFN. 25 Our analysis now identifies IFN-a5 as an IRF-3-dependent direct response gene. The IFNs are secreted from infected cells and thereby disseminate immune response signals to other cells of the body.…”
Section: Irf-3-dependent Direct Response Genesmentioning
confidence: 99%
“…Furthermore, the kinetics of IRF in response to poly I:C may be limiting the longevity of any effects on type I IFN expression. Marie and colleagues compared the magnitude and kinetics of IFN secretion 37. Infection of WT embryo fibroblasts with Newcastle disease virus (NDV) or RNA resulted in the rapid production of high levels of IFN α with a peak at 6–8 h.…”
Section: Resultsmentioning
confidence: 99%